Analysis of Projected Temperature Changes in Aceh Province - Ilhamsyah, Yopi; Rahmy, Yustya; Marwan, Marwan; Kadarsah, Kadarsah (POSITRON, 2023)
The objective is to analyse temperature changes and their future projection in Aceh. The activities consist of collecting past and future temperature data, preparing materials for processing, and analyzing past and future temperature data (climate change projections). The data used are monthly average temperature data from data global climate model, e.g., csiromk3.6-hist-1986-2005-tas, csiromk3.6-rcp45- 2016-2035-tas, csiromk3.6-rcp45-2046-2065-tas, csiromk3.6-rcp45-2081-2100- tas, csiromk3.6-rcp85-2016-2035-tas, csiromk3.6-rcp85-2046-2065-tas, and csiromk3.6-rcp85-2081-2100-tas. The study began with reading climate data in NetCDF format using GRADS software, data processing using CDO software, providing a coordinate system using QGIS software, making climate change projection maps using ArcGIS software, and making climate change graphs using spreadsheet programs. Two scenarios, i.e., RCP4.5 and RCP8.5 are used to analyse the projected temperature changes in the short-term (2016 – 2035), medium-term (2046-2065), and long-term (2081-2100). The results show that the RCP4.5 projection shows a lower change in temperature rise than the RCP 8.5. A change in a temperature rise of up to 5°C was found in the RCP8.5 scenario.